2019
DOI: 10.1097/md.0000000000017498
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and predictive factors analysis for efficacy and safety of Kirschner wire, anatomical plate fixation and cannulated screw in treating patients with open calcaneal fractures

Abstract: This study aimed to compare the efficacy and safety among Kirschner wire, anatomical plate fixation and cannulated screw treatments in patients with open calcaneal fractures, and to explore the predictive factors for treatment response and complication occurrence.The 142 open calcaneal fracture patients were enrolled in this study, who received fixation procedures of Kirschner wire, anatomical plate fixation or cannulated screw on demand. Treatment efficacy was assessed by AOFAS score and occurrence of complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In our opinion, the main reason for this may be due to the high-order aberrations triggered in patients who received FS-LASIK and structural changes caused by the creation of a corneal flap. Indeed, past studies have demonstrated that higher-order optical aberrations and systematic changes in corneal topography can be associated with uncomplicated lamellar flap creation (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, the main reason for this may be due to the high-order aberrations triggered in patients who received FS-LASIK and structural changes caused by the creation of a corneal flap. Indeed, past studies have demonstrated that higher-order optical aberrations and systematic changes in corneal topography can be associated with uncomplicated lamellar flap creation (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its rarity, knowledge about treating open calcaneal fractures is based on small case series (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) . The first studies showed a bleak scenario with complication rates above 60%, including lower limb amputations in 29% and osteomyelitis in 19%-39% of cases (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) .…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we assess the outcomes of 12 patients with complex type VI tibial plateau fractures who were treated with the DRTR. The purpose of this study is to assess the efficacy of the DRTR surgical technique as a minimally invasive treatment of type VI tibial plateau fractures and to demonstrate the safety and efficacy of this technique by roughly comparing it with those associated with common-sense open internal fixation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%